'Oncokompas', a web-based self-management application to support patient activation and optimal supportive care: a feasibility study among breast cancer survivors. (3rd July 2018) - Melissant, Heleen C.; Verdonck-de Leeuw, Irma M.; Lissenberg-Witte, Birgit I.; Konings, Inge R.; Cuijpers, Pim; Van Uden-Kraan, Cornelia F.
Abstract: Background: Cancer survivors have to deal with symptoms related to cancer and its treatment. In Oncokompas, cancer survivors monitor their quality of life by completing patient reported outcome measures (PROMs), followed by personalized feedback, self-care advice, and supportive care options to stimulate patient activation. The aim of this study was to investigate feasibility and pretest–posttest differences of Oncokompas including a newly developed breast cancer (BC) module among BC survivors. Material and methods: A pretest–posttest design was used. Feasibility was investigated by means of adoption, usage, and satisfaction rates. Several socio-demographic and clinical factors, and health-related quality of life (HRQOL) were explored that might be associated with patient satisfaction. Barriers and facilitators of Oncokompas feasibility were investigated by evaluating nurse consultation reports. Differences in patient activation (Patient Activation Measure) and patient-physician interaction (Perceived Efficacy in Patient–Physician Interactions) before and after Oncokompas use were investigated. Results: In total, 101 BC survivors participated. Oncokompas had an adoption rate of 75%, a usage rate of 75–84%, a mean satisfaction score of 6.9 (range 0–10) and a Net Promoter Score (NPS) of −36 (range −100–100) ( N  = 68). The BC module had a mean satisfaction score of 7.6. BC survivors who received surgery including chemotherapy and/or radiotherapy were significantly more satisfied with Oncokompas than BC survivors with surgery alone ( p  = .013). Six facilitators and 10 barriers of Oncokompas feasibility were identified. After using Oncokompas, BC survivors scored significantly higher on patient activation ( p  = .007; r  = .24), but not on patient-physician interaction ( p  = .75). Conclusion: Oncokompas including a BC module is considered feasible, but needs further optimization to increase user satisfaction. This study shows the value of tailoring eHealth applications for cancer survivors to their specific tumor type. Oncokompas including the BC module seems to improve patient activation among BC survivors.